How to Avoid Posterior Interosseous Nerve Injury During Single-Incision Distal Biceps Repair Drilling. Issue 2 (February 2019) - Becker, David; Lopez-Marambio, Francisco Antonio; Hammer, Niels; Kieser, David
Abstract: Background: The posterior interosseous nerve (PIN) is occasionally damaged during distal biceps tendon repair. But to our knowledge, no studies have examined the position of the PIN in relation to the bicipital tuberosity in full supination, which is the recommended position during single-incision distal biceps repair or reconstruction Questions/purposes: (1) What is the anterior safe zone when exposing the anterior tuberosity with the arm in supination? (2) When drilling the radial tuberosity for bicortical button placement in full supination, how should the drill be angled to avoid PIN injury? Methods: Fifteen adult cadaver elbows had the PIN dissected around the proximal radius. The position of the PIN was measured relative to the most ulnar aspect of the radius at three sites in full supination: at the bicipital tuberosity (bicipital tuberosity-PIN), 10 mm proximal to the bicipital tuberosity (bicipital tuberosity-proximal), and 10 mm distal to the bicipital tuberosity (bicipital tuberosity-distal). We made another measurement by drawing a line from the lateral humeral epicondyle to the radial styloid. The point where the PIN intersects this line, when viewed laterally and measured from the lateral humeral epicondyle, was marked and measured to indicate where it wraps around the radius laterally (PIN-lateral). The last measurement (bicipital tuberosity-lateral) was made where the line from the lateral humeral epicondyle to the radial styloid intersected the position of the bicipital tuberosity. This was determined by the point where a perpendicular line from the bicipital tuberosity was drawn laterally to meet with the lateral line. We did this to establish if the PIN adopts its most lateral position on the radius at the same level as the bicipital tuberosity. Results: The anterior safe zone in the approach to the biceps tuberosity extends approximately 15 mm from its prominence (mean, 20.7 mm; range, 16.0–24.1 mm). The PIN crosses the lateral midline from anterior to posterior at 46.0 mm (range, 31.2–67.0 mm) from the lateral epicondyle (lying directly opposite the bicipital tuberosity at nearly the same level); therefore, the drill exit should be posterior to lateral midline while aiming proximally to the bicipital tuberosity. Conclusion: Our anterior safe zone found that the PIN travels from an anterior position on the radius, when measuring 1 cm proximal to the bicipital tuberosity to a lateral position on the radius at the level of the bicipital tuberosity prominence (on the contralateral cortex), to a slightly more posterior position on the radius 1 cm distal to the bicipital tuberosity. Typically, the PIN sits directly opposite the biceps tuberosity, often directly on the cortex of the radius when the forearm is in full supination. Clinical Relevance: Because of these findings, perpendicular bicortical drilling starting at the bicipital tuberosity should be avoided. A more proximal and ulnar drilling angle is recommended. Defining a safe zone for an anterior approach seems to be clinically unhelpful due to the high anatomical variability that exists for the position of the PIN around the proximal radius. Future studies could attempt to confirm our findings with the analysis of noncadaveric imaging in three different planes using such modalities as MRI to avoid the effects of tissue distortion during cadaveric preparation and dissection.